Severe hypovitaminosis D correlates with increased inflammatory markers in HIV infected patients - Ansemant Thiphaine; Mahy Sophie; Piroth Christine; Ornetti Paul; Ewing Stephanie; Guilland Jean-Claude; Croisier Delphine; Duvillard Laurence; Chavanet Pascal; Maillefert Jean-Francis; Piroth Lionel (BMC Infectious Diseases, 2013)
Abstract Background Even though it has been suggested that antiretroviral therapy has an impact on severe hypovitaminosis D (SHD) in HIV infected patients, it could be speculated that the different levels of residual inflammation on HAART (Highly Active Anti Retroviral Therapy) could contribute to SHD and aggravate bone catabolism in these patients. Methods A cross-sectional study was carried out in an unselected cohort of 263 HIV infected outpatients consulting during Spring 2010. Clinical examinations were performed and medical history, food habits, sun exposure and addictions were collected. Fasting blood samples were taken for immunological, virological, inflammation, endocrine and bone markers evaluations. Results Ninety-five (36%) patients had SHD. In univariate analysis, a significant and positive association was found between SHD and IL6 (p = 0.001), hsCRP (p = 0.04), increased serum C-Telopeptides X (CTX) (p = 0.005) and Parathyroid Hormon (PTH) (p < 0.0001) levels. In multivariate analysis, SHD deficiency correlated significantly with increased IL-6, high serum CTX levels, lower mean daily exposure to the sun, current or past smoking, hepatitis C, and functional status (falls), but not with the time spent on the current HAART (by specific drug or overall). Conclusions SHD is frequent and correlates with inflammation in HIV infected patients. Since SHD is also associated with falls and increased bone catabolism, it may be of interest to take into account not only the type of antiretroviral therapy but also the residual inflammation on HAART in order to assess functional and bone risks. This finding also suggests that vitamin D supplementation may be beneficial in these HIV-infected patients.